LABORATORY RESEARCH OF HORMONAL STATUS IN PREGNANT WOMEN WITH OBESITY - Myalyuk, O. P.; Marushchak, M. I.; Shtrimaitis, O. V.; Golyb, O. I.; Pystovit, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
During the physiological course of pregnancy, hormones are in equilibrium, providing adequate implantation and placental placement, necessary for the further normal development of the fetus. The most significant changes concern hormone-estrogen fraction and progesterone in pregnant women. The purpose of the study was to identify and assess laboratory parameters of hormonal background in pregnant women with obesity. 60 pregnant women with constitutional obesity were examined from 2018 to 2019. The patients were divided into two subgroups: I subgroup - 30 patients whom we prepared for pregnancy and conducted the entire gestational period, II subgroup -30 pregnant women were examined and received the necessary therapeutic and preventive measures only from the moment of treatment. The control group was composed of 20 pregnant women with a physiological course of the gestational period. For the evaluation of hormonal status, the determination of estradiol (E), progesterone (PG), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), as well as the chorionic gonadotropin (HG) and placental lactogen (PL) was carried out. We found that obese pregnant women had a significant reduction in the level of these hormones compared to healthy pregnant women, so the choice of obstetric tactics in pregnant women with obesity should be carried out according to their values. In addition, the determination of hormone level disorders allows to predict the development of severe complications already in the I trimester to the appearance of the first clinical and laboratory symptoms. Despite the high risk of complications in pregnant women with excessive body weight, obesity is not a contraindication to pregnancy.